Efeitos de não comutatividade em matéria condensada - Santos, Willien Oliveira dos (2016)
Using the method of the star product, the non-relativistic regime of the Dirac equation is evaluated and the NC hamiltonian to the Zeeman e ect is determined. Using the rst-order perturbation theory, the correction to the energy is calculated. We obtain the orbital and spin Land e factors. It is shown that the experimental value for the spin Land e factor put the following upper limit on the magnitude of the momentum NC parameter, p . 0; 34 eV=c. Established also a possible correction of the NC phase space to the presently accepted value of Planck's constant with an uncertainty of 2 part in 1035. By mapping via Boop's shift we obtain the Landau levels and the Hall conductivity for graphene in NC phase space. Using the current experimental precision, respectively, of the Hall conductivity and of the Landau levels in graphene, we obtain the following upper limit to the magnitude of the momentum NC parameter, p . 2; 5eV=c e p . 8; 5eV=c. Finally, by Newton's law in NC space and using the Langevin equations, we describe the Browniano motion, and thus we de ne a new physical parameter that shows the possibility of detecting NC eff ects on the macroscopic scale.